2013
DOI: 10.4103/2230-8210.119512
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary infection in diabetes

Abstract: Diabetes is known to increase the risk of infection and the commonest amongst them are the ones involving the genitourinary tract. The infections in a diabetic patient are unique in that they are recurrent, more severe, requiring hospitalization, and also have higher mortality than nondiabetics. Some infections are exclusively found in diabetics like the emphysematous pyelonephritis while others have their natural history complicated due to hyperglycemia. Asymptomatic bacteriuria may lead to albuminuria and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…Obesity and DM have also shown a strong association [20]. A higher BMI in turn has been found to have a significant correlation with poorer outcomes [21–23]. The BMI classification in our present study was based on the WHO grading for the Asian population [24].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and DM have also shown a strong association [20]. A higher BMI in turn has been found to have a significant correlation with poorer outcomes [21–23]. The BMI classification in our present study was based on the WHO grading for the Asian population [24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the highest risk ratio was found in genital diseases, which may www.nature.com/scientificreports/ be related to the high prevalence of genital diseases in women. For example, diabetic women are more likely to develop vulvovaginal and pelvic infection 26,27 , and insulin deficiency followed by poor metabolic control results in reproductive dysfunction with decreased female hormones 28 . It is accepted that edema can occur in patients treated with TZD.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies reported till now focused on hyperglycaemia and its relation to the effects on male fertility. Hyperglycaemia can increase the risk of urino‐genital tract infections (Julka, ; Njomnang Soh et al, ), and the mechanisms that contribute to this increased risk have not received much attention, especially on the innate immune responses. Hence, we attempted to study the expression pattern of innate immune receptors ( Tlr1 ‐13 and Nod1 /2) in the male reproductive tract of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%